Perbandingan Pertanggungjawaban Hukum antara Bentuk Badan Usaha Terbatas (PT) dan Perusahaan Perorangan - Naily Aridah; Rewidan Muhammad Haikal (Journal of Management and Bussines (JOMB), 2024)
The aim of the research is to identify the comparison of legal liability between limited business entities (PT) and individual companies. This research uses a normative legal approach with descriptive analysis characteristics. Data collection was carried out through secondary data sources, specifically by applying library research techniques, known as "Library Research." The research results show differences in legal liability between PT and individual companies. PT shareholders have limited liability, while individual company owners have limited liability for the value of their shares, in accordance with the principle of limited liability. In conclusion, this research provides in-depth insight into the legal aspects that differentiate the responsibilities of PT and individual companies. These findings can be the basis for developing legal policies that are more effective in regulating the legal responsibilities of business entities, whether in the form of PT or individual companies. Keywords: Comparison, Accountability, PT, Individual